High Soluble Programmed Death-Ligand 1 Predicts Poor Prognosis in Patients with Nasopharyngeal Carcinoma - Lu, Tianzhu (Onco Targets Ther, 2020)
PURPOSE: Immune checkpoint proteins in the tumor microenvironment can enter the blood circulation and are potential markers for liquid biopsy. The aims of this study were to explore differences in immune checkpoint protein expression between patients with nasopharyngeal carcinoma (NPC) and healthy controls and to investigate the prognostic value of the soluble form of programmed death-ligand 1 (sPD-L1) in NPC. METHODS: In total, 242 patients were included in the disease group. Plasma samples from 23 NPC patients and 15 healthy control were used for immune checkpoint protein panel assays. Samples from 219 patients with NPC including 30 paired pre-treatment and post-radiotherapy samples were evaluated by enzyme-linked immunosorbent assay to determine sPD-L1 levels. RESULTS: A total of 14 immune checkpoint proteins, including sPD-L1were upregulated in 23 patients with NPC (all p<0.001) compared with 15 healthy controls. Among 219 patients, the median follow-up time was 50 months (7–82 months). Based on the optimal cutoff value of 93.7 pg/mL, patients with high expression of sPD-L1 had worse distant metastasis-free survival (87.5% vs 74.0%, p=0.006) than those of patients with low expression. Multivariate analysis showed that sPD-L1 (HR=1.99, p=0.048) and EBV-DNA (HR=2.51, p=0.030) were poor prognostic factors for DMFS. In the group with high EBV-DNA expression, DMFS was worse for patients with high sPD-L1 expression than those with low sPD-L1 expression (56.4% vs 82.6%, p=0.002). CONCLUSION: Plasma immune checkpoint protein expression differed significantly between patients with NPC and healthy donors. Plasma sPD-L1 levels are a candidate prognostic biomarker, especially when combined with EBV-DNA.